2005
DOI: 10.1161/01.atv.0000150039.60906.02
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms of the Interleukin-1β Gene Affect the Risk of Myocardial Infarction and Ischemic Stroke at Young Age and the Response of Mononuclear Cells to Stimulation In Vitro

Abstract: on behalf of IGIGI InvestigatorsObjectives-To investigate the role of interleukin-1␤ (IL-1␤) gene polymorphisms as a link between inflammation, coagulation, and risk of ischemic vascular disease at young age. Methods and Results-A total of 406 patients with myocardial infarction (MI) at young age, frequency-matched for age, sex, and recruitment center, with 419 healthy population-based controls and 134 patients with ischemic stroke at young age, matched by age and sex, with 134 healthy population-based control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
117
2
14

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 148 publications
(145 citation statements)
references
References 31 publications
10
117
2
14
Order By: Relevance
“…Recruitment of the Italian and US MI populations has been described elsewhere [16,18,19] (see Appendix S1). Patients with first-ever ischemic stroke (n = 267) occurring before the age of 45 years, consecutively admitted to the Department of Neurology, University of Brescia, and control subjects (n = 212) recruited from the general population in the area surrounding the medical centre, with no known history of vascular disease, frequency-matched to the cases by sex and age, were included in the study [20].…”
Section: Study Populationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recruitment of the Italian and US MI populations has been described elsewhere [16,18,19] (see Appendix S1). Patients with first-ever ischemic stroke (n = 267) occurring before the age of 45 years, consecutively admitted to the Department of Neurology, University of Brescia, and control subjects (n = 212) recruited from the general population in the area surrounding the medical centre, with no known history of vascular disease, frequency-matched to the cases by sex and age, were included in the study [20].…”
Section: Study Populationsmentioning
confidence: 99%
“…Our group have previously demonstrated that genetic variations of IL-1B were associated with the risk of both myocardial infarction and ischemic stroke at young age by affecting the release of IL-1B from stimulated mononuclear cells and in turn the expression of TF on cell membranes [16,17]. The aim of the present study was to evaluate the possible contribution to MI and/or ischemic stroke of tag-haplotypes in the TF gene in four case-control studies from different populations.…”
mentioning
confidence: 91%
“…Previous evidence supports our findings. IL-1B rs1864169 and rs3136558 have been indicated in various cerebrovascular phenotypes, such as stroke, ischemic injury and aneurysmal rupture (Boutin et al, 2001;Iacoviello et al, 2005;Slowik et al, 2006). These findings suggest that the IL-1B polymorphism is involved in the development of ischemic stroke.…”
Section: Discussionmentioning
confidence: 83%
“…18 The same genetic variants were found to be associated with either circulating levels of TF 41 or TF release from circulating lymphomonocytes. 19 Moreover, TF gene promoter haplotypes were associated with carotid intima-media thickness, a condition predisposing to ischemic stroke. 44 According to the principle of Mendelian randomization, 45 circulating TF should be considered more a causal risk factor for stroke rather than a marker of unrecognized exogenous factors.…”
Section: Discussionmentioning
confidence: 99%
“…A report from the European Prospective Investigation into Cancer and Nutrition (EPIC)-Norfolk study, indeed, evaluating the association between serum levels of TF and the risk of future coronary events in apparently healthy individuals, could not find any independent association. 17 Using a candidate gene approach, 18 we found that TF gene polymorphisms, associated with TF expression from human monocytes stimulated by LPS, 19 were associated with the risk of ischemic stroke at young age, whereas they did not affect ischemic coronary disease.…”
Section: Strokementioning
confidence: 99%